Non-malignant asbestos pleural disease. Issue 9 (September 1981) - Hillerdal, G
Abstract : During a 10-year period (1970-79) all patients in Uppsala County found to have pleural changes related to asbestos exposure were followed. The lesions could be divided into four types: parietal pleural plaques, exudative pleurisy, thickening of the visceral pleura, and progressive pleural fibrosis. There were 891 cases. The most common type was parietal plaques, which was seen in 827 patients, some of whom later developed other changes. In 22 types exudation was proven radiologically, and in 84 more cases obliteration of the costo-phrenic angle was seen. The exudations almost all had a benign course, despite sometimes fairly large and bloody effusions. They were practically all symptom-free, being a surprise finding on chest radiography. Thickening of the visceral pleura can only be seen radiologically in the fissures and occurred in a few cases in addition to other changes. In a small group of more heavily exposed individuals, a progressive pleural fibrosis developed, sometimes after an initial effusion.